Explosive HIV-1 subtype B' epidemics in Asia driven by geographic and risk group founder events - Li, Y.; Uenishi, R.; Hase, S.; Liao, H.; Li, Xiao-Jie; Tsuchiura, T.; Tee, K.K.; Pybus, O.G.; Takebe, Y. (Elsevier, 2010)
We explored the timescale, spatial spread, and risk group population structure of HIV-1 subtype B', the cause of explosive blood-borne HIV-1 epidemics among injecting drug users (IDUs) and former plasma donors (FPDs) in Asia. Sequences from FPDs in China formed a distinct monophyletic cluster within subtype B'. Further analysis revealed that subtype B' was founded by a single lineage of pandemic subtype B around 1985. Subsequently, the FPD cluster appears to have derived from a single subtype B' lineage around 1991, corroborating the hypothesis that FPD outbreaks stemmed from the preceding epidemic among IDUs in Southeast Asia, most likely from the Golden-Triangle region. (C) 2010 Elsevier Inc. All rights reserved.